1996
DOI: 10.1101/gad.10.16.2055
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the p53 and SCID genes cooperate in tumorigenesis.

Abstract: DNA damage can cause mutations that contribute to cellular transformation and tumorigenesis. The p53 tumor suppressor acts to protect the organism from DNA damage by inducing either G1 arrest to facilitate DNA repair or by activating physiological cell death (apoptosis). Consistent with this critical function of p53, mice lacking p53 are predisposed to developing tumors, particularly lymphoma. The severe combined immune deficiency (scid~ locus encodes the catalytic subunit of DNA protein kinase (DNA-PKcs), a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(128 citation statements)
references
References 43 publications
(51 reference statements)
10
116
2
Order By: Relevance
“…Elevated steady state level of p53 protein in the scid thymus Two previous studies reported ®nding higher levels of p53 protein in scid thymocytes than in normal thymocytes (Guidos et al, 1996;Nacht et al, 1996). Higher levels of p53 protein were detected in scid thymocytes but not in scid splenocytes (primarily myeloid cells) suggesting that the thymocyte-speci®c up-regulation of p53 protein could be the result of V(D)J-speci®c double-stranded DNA breaks that accumulate in these cells.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Elevated steady state level of p53 protein in the scid thymus Two previous studies reported ®nding higher levels of p53 protein in scid thymocytes than in normal thymocytes (Guidos et al, 1996;Nacht et al, 1996). Higher levels of p53 protein were detected in scid thymocytes but not in scid splenocytes (primarily myeloid cells) suggesting that the thymocyte-speci®c up-regulation of p53 protein could be the result of V(D)J-speci®c double-stranded DNA breaks that accumulate in these cells.…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies showed that the level of p53 protein was elevated in scid thymocytes relative to normal cells and suggested that this was due to the accumulation of double-stranded breaks in DNA resulting from failed attempts at V(D)J recombination in scid lymphocytes (Guidos et al, 1996;Nacht et al, 1996). The persistence of DNA recombination intermediates and the high abundance of p53 protein within the same cell population suggested that p53 may be involved in the detection of abnormal recombination intermediates and in the subsequent elimination of such clones.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a single treatment of newborn scid mice with DNA-damaging agents restored functional, diverse T cell receptor b chain coding joints, as well as development and di erentiation of thymocytes, but did not promote B cell development (Danska et al, 1994). In addition, p53 de®ciency promoted T cell development but did not appear to circumvent the block in B cell maturation conferred by the scid mutation Nacht et al, 1996). All these data provide evidence that the later steps involved in V(D)J joining are not regulated identically, in T and B cells.…”
Section: Role Of the Ku86 Variant In B Cell DI Erentiationmentioning
confidence: 99%
“…It may be possible that initially different kind of tumor cells originate in p53 À/À mice, but the immunogenic tumors are eliminated by T-cell-mediated immune responses in these mice and only tumor cells that could escape the heightened T-cell immunogenic responses develop into full blown tumors. This hypothesis is supported by the earlier finding that p53 À/À RAG1 À/À , p53 À/À RAG2 À/À and p53 À/À SCID mice develop lymphomas at much higher frequency and at a faster rate with short latency than p53 À/À mice [20,32,33]. Some of the conditions that may favor the immune escape of lymphomas in p53 À/À mice include (i) their initial development inside the immunologically privileged site (e.g.…”
Section: P53 à/à Mice Are Resistant To Transplanted Tumorsmentioning
confidence: 55%
“…Eradication of tumors also involves immune cells, and systemic drug administration may lead to activation of p53 pathways in many cell types, including T cells. Also, p53 À/À Rag1 À/À or p53 À/À SCID mice develop lymphomas at a much faster rate than p53 À/À , suggesting a role for mature T cells in delayed development of lymphomas in p53 À/À mice [20,32,33]. Therefore, in light of the data presented here, it is imperative to determine the role of p53 in anti-tumor T-cell responses.…”
mentioning
confidence: 99%